Lrrk2 R1628P variant is a risk factor for essential tremor - Chao, Yin Xia (Sci Rep, 2015)
Essential tremor (ET) and Parkinson's disease (PD) are two of the most common adult onset movement disorders with overlapping clinical features. PD patients with leucine-rich repeat kinase-2 (LRRK2) mutations may present initially with an ET phenotype. To address the possibility of a common genetic link between ET and PD, we examined the association between a common LRRK2 R1628P gene variant and ET. The LRRK2 R1628P was genotyped in ET cases and matched healthy controls. A total of 1277 subjects comprising of 450 ET cases and 827 controls were included. There were 40 heterozygote (GG to CG) variant out of 450 ET cases (genotypic frequency 8.9%) and 36 heterozygote variant (GG to CG, genotypic frequency 4.3%) and one homozygote variant (GG to CC) out of 827 controls. Subjects carrying the R1628P variant had a twofold increased risk of ET (p = 0.0035, OR = 2.20 and 95% confidence interval is 1.30–3.73). Using a case control methodology, we demonstrated an association between a known PD risk variant, LRRK2 R1628P, with ET. Subjects carrying the R1628P variant had twice the risk of developing ET. The sharing of a similar gene risk variant suggests a possible pathophysiologic link between PD and ET.